Hubungan Pengetahuan Ibu Tentang Pertumbuhan Gigi dengan Kasus Persistensi pada Anak Usia 7-1 Tahun di Wilayah Kerja Puskesmas Mangasa - Zahrawi Astrie Ahkam; Amirah Maritsa; Hasrini Hasrini; Pariati Pariati; Zulkarnain Zulkarnain (Universitas Muhamadiyah Manado, 2022)
Objective: Over-retained tooth is condition when the primary tooth as retainer of the permanent tooth not exfoliate promptly, while permanent tooth has been erupted. The oral health problems in Makassar reported anomalies of tooth development and eruption were in the second place with 8.897 cases in 2018. Mangasa Public Health Center (PHC) possessed the highest number of over-retained tooth cases which becomes their primary problem in this category. Children's oral and dental health particularly over-retained tooth is largely determined by the awareness of their mothers’ behaviour and knowledge. The purpose of this study was to determine the correlation between mothers’ knowledge towards dentition and over-retained tooth during mixed dentition case on children aged 7-11 years in Mangasa PHC area. Method: This study was analytical observation research with cross sectional design. There were 106 samples of children aged 7-11 years together with their mothers in Mangasa PHC obtained by using simple random sampling. Data were collected through questionnaire and children's oral examination. Data were analyzed by the ChiSquare test. The results of this study showed that 54.7% of children in Mangasa PHC area had over-retained tooth. The high level of mother's knowledge about dentition was 55.7% Result: The results of the analysis between the mother's knowledge of dentition and over-retained tooth obtained value of p = 0,0001. Conlusion: There was a significant correlation between mothers knowledge of dentition and occurrence of over-retained tooth among children aged 7-11 years in Mangasa PHC area.